2012
DOI: 10.1103/physreva.86.053410
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effects in strong-field ionization: Energy shifts and Rydberg structures

Abstract: The behavior of strong-field ionization rates of neutral atoms in the vicinity of multiphoton ionization thresholds is analyzed using formal collision theory. Our approach, which accounts nonperturbatively for effects of an intense laser field, shows that the ionization rates have a nearly constant behavior below and above each multiphoton threshold and that between such thresholds there are an apparently finite number of rapid oscillations due to resonances with laser-field-modified Rydberg states. This patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…For comparison, we also show the probability of ionization in the adiabatic limit. The behavior of the ionization probability is very similar to the behavior of the ionization rate evaluated within Floquet theory [19,20] with one striking difference. According to Floquet theory, the ionization potential and therefore the number of photons required to ionize the atom increases with peak intensity due to the AC-Stark shift of the atomic levels.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…For comparison, we also show the probability of ionization in the adiabatic limit. The behavior of the ionization probability is very similar to the behavior of the ionization rate evaluated within Floquet theory [19,20] with one striking difference. According to Floquet theory, the ionization potential and therefore the number of photons required to ionize the atom increases with peak intensity due to the AC-Stark shift of the atomic levels.…”
Section: Resultssupporting
confidence: 59%
“…(1)), the behavior of the ionization probability is qualitatively similar : a smooth region followed by a region of isolated (Freeman type) resonances and a broad hilly structure. However, in [19,20], it was shown that the behavior of the ionization rate is nearly constant just below and above each N-photon threshold. This contrasts with the behavior of the ionization probability shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[18], the positions of the maxima of these oscillations depend on the shape of the atomic potential: For a short-range potential they coincide with the positions of multiphoton thresholds [16], whereas the corresponding peaks for a Coulomb potential occur in the middle between two neighboring multiphoton thresholds [18]. (Similar features have been found in strongfield ionization of an electron in a Coulomb potential [21]). …”
Section: Introductionmentioning
confidence: 51%
“…Theoretical analysis of the angular momentum distribution in the populated Rydberg states is less advanced. Predictions of Floquet theory for a monochromatic laser field [35] and results of numerical calculations for laser pulses with a trapezoidal envelope [32] yield that the angular momentum of the excited Rydberg states has the same parity as N p − 1, where N p is the minimum number of photons needed to ionize the atom. Furthermore, the angular quantum number of the states with the largest population in numerical calculations [9,10,32] agrees well with semiclassical estimations [36], initially performed for low-energy angular resolved photoelectron distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies of the excitation mechanism in strong fields mainly consider the distribution of the population as a function of the principal quantum number of the excited states [9,10,25,31,32]. It was shown that the modulation of the excitation probability is related to the channel closing effect [9,10,32,35]. The latter phenomenon occurs at threshold intensities at which the absorption of one more photon is needed to ionize the atom due to the shift of the ionization threshold by the ponderomotive energy.…”
Section: Introductionmentioning
confidence: 99%